Implementation of Problem Based Learning (PBL) Model to Increase Students' Interest in Learning Spatial Building Material in Class VII of SMP Negeri 5 Kisaran - Hasibuan, Syarinah Junianti; Sipakkar, Tari Rodearna Br; Helmira, Tiara; Pardosi, Marlina Friska Nova; Anim, Anim (Holistic Science, 2024)
The purpose of this study was to determine the results of increasing students' interest in learning mathematics on the material of building space by using the Problem Basset Learning (PBL) learning model. This research uses the method of classroom action research (PTK) or action research. According to Arikunto (2010: 1). Classroom action research is research that describes the cause-and-effect of treatment, as well as describes what happens when treatment is given, and describes the entire process from the beginning of the treatment to the impact of the treatment. The subjects used in this study were students of class VII-2 SMP N 5 Kisaran with a total of 32 students. The data in this study are test results and observation results. The results showed that using the PBL (Problem Based Learning) model can increase students' interest in learning mathematics on the material of building space. In cycle I consisting of 32 students, where 25 students (78%) in class VII-2 have increased students' interest in learning mathematics, while in cycle II with 29 students (91%) has greatly increased students' interest in learning while only 3 students (9%) still have not increased their interest in learning mathematics.